2003
DOI: 10.2320/matertrans.44.2529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetic Field and Prior Austenite Grain Size on the Structure Formed by Reverse Transformation from Lath Martensite to Austenite in an Fe-0.4C Alloy

Abstract: Effects of magnetic field strength and prior austenite grain size on the microstructure formed by the reverse transformation from lath martensite to austenite have been investigated in Fe-0.4C alloy. The degree of elongation of reverse-transformed austenite increases with increasing applied magnetic field, which is a similar result with that for austenite to ferrite transformation. However, well-elongated austenite is formed not only in small prior austenite grains but also in relatively large prior austenite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…With a maximum magnetic field of 10 T, the transformation temperature is about 914.9 C, which is 8. 7 C higher than that without magnetic field. The increased temperature (ÁT ¼ TðHÞ À Tð0Þ), the transformation temperature difference between with (TðHÞ) and without (Tð0Þ) a magnetic field (H) was plotted against magnetic field strength in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…With a maximum magnetic field of 10 T, the transformation temperature is about 914.9 C, which is 8. 7 C higher than that without magnetic field. The increased temperature (ÁT ¼ TðHÞ À Tð0Þ), the transformation temperature difference between with (TðHÞ) and without (Tð0Þ) a magnetic field (H) was plotted against magnetic field strength in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…In recent years, the effects of strong magnetic fields on various phase transformations in steels, including martensite [15,16], bainite [17,18], ferrite [19,20] and pearlite [21] transformations have attracted much research interest. It is usually considered that strong magnetic field has a significant influence on ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Chiba et al [58] reported that a Co-Ni-based superalloy aged in a magnetic field exhibits higher strain-age hardening. Ohtsuka et al [59] investigated the transformed structure in a reverse transformation from lath martensite to austenite in a magnetic field and observed an elongated and aligned structure. Watanabe et al [60] spot-welded stainless steel in a magnetic field and observed the structure of the heat-affected zone (HAZ) and found that the area of the HAZ increases with increasing magnetic field.…”
Section: Other Transformations In a Magnetic Fieldmentioning
confidence: 99%